2020
DOI: 10.2166/wst.2020.545
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient and cheap treatment of dye by graphene-doped TiO2 microspheres

Abstract: Highly efficient dye wastewater treatment by photocatalytic catalysis commonly requires expensive catalysts, long time degradation and complicated procedure. Here, we for the first time prepared the cheap graphene-doped TiO2 microspheres with simple procedure to degrade dye with high efficiency. When the catalyst concentration was 0.2 g·L−1, the photocatalysis degradation extent of methylene blue solution, methylene green solution and 1, 9-dimethyl methylene blue solution reached 96.4, 85.9 and 98.7%, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Seldomly reported, the photocatalysts are susceptible to mechanical stress and eventual fracture caused by the stirring in the batch reactor, generating smaller particles and a higher surface area, which overestimates the photocatalytic performance and jeopardizes the claimed easy removal of the photocatalysts after a test. Also, porosity data, like specific surface area and pore diameter, are not properly discussed or even totally or partially missing in some papers in the literature [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], neglecting possible synergies and effects granted by the catalytic supports in what regards, e.g., mass transfer. Concerning the particle size, most of the reported microspherical supports are usually very small, ranging from 0.5 to 3 µm [ 18 , 19 , 20 , 21 , 23 , 24 , 25 ], which may impose problems and extra complexity and costs in a real-life application, in what regards the setup and recovery aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Seldomly reported, the photocatalysts are susceptible to mechanical stress and eventual fracture caused by the stirring in the batch reactor, generating smaller particles and a higher surface area, which overestimates the photocatalytic performance and jeopardizes the claimed easy removal of the photocatalysts after a test. Also, porosity data, like specific surface area and pore diameter, are not properly discussed or even totally or partially missing in some papers in the literature [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], neglecting possible synergies and effects granted by the catalytic supports in what regards, e.g., mass transfer. Concerning the particle size, most of the reported microspherical supports are usually very small, ranging from 0.5 to 3 µm [ 18 , 19 , 20 , 21 , 23 , 24 , 25 ], which may impose problems and extra complexity and costs in a real-life application, in what regards the setup and recovery aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Since discovering the ability of TiO 2 electrodes on water splitting by Fujishima & Honda 1972, heterogeneous semiconductor photocatalysis has been broadly utilized in various fields, including water purification, selective organic transformations, and CO 2 reduction (Wen et al 2017). However, due to the large bandgap of TiO 2 (3.2 eV) and low sensitivity towards visible light (Liang et al 2021); the potential of other semiconductors such as ZnO, ZnS, BiVO 4 , g-C 3 N 4 , CdS, CdSe were explored. Zou et al (2000) reported the suitability of InNbO 4 and InTaO 4 with bandgap energy of 2.5 eV and 2.6 eV as photocatalysts.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%